Because my name blossoms my bisabuela - Leaños, Angelina (Northridge Review, 2025)
Angelina Leaños (she/her) is a Ventura County Youth Poet Laureate Emeritus and a second-year MFA student at Fresno State. Angelina regularly serves as a Poetry Out Loud coach and a Poet-Teacher, mentoring youth in poetry recitation and creative writing. Additionally, Angelina is a member of California Poets in the Schools’ Board of Directors and was a reader for the 2023 Philip Levine Prize. Her work has been published by Urban Word, Flowersong Press, the Chicanx Writers & Artists Association, Arkana, and Fruitslice. You can find her on Instagram at @angelinaleanos.